Peningkatan Keterampilan Berpikir Kritis Melalui Pengembangan E-Modul Perpajakan Berbasis Case Method - Nita Sofia; Mentari Ritonga; Sri Arita; Syahrul Syahrul; Mir Atun Shalihah; Ika Parma Dewi; Rani Sofya (Universitas Negeri Padang, 2023)
To develop e-modul for Tax course with case-based method to increase students’ critical thinking skill. It is a research and development research (R&D). E-modul of Tax course has been developed using 4D design (Define, Design, Develop, and Disseminate) with case-based method to increase students’ critical thinking skill.